Grammatical Mechanisms of Pragmatization in Russian and Uzbek Phraseology: Mekanisme Gramatikal dalam Pragmatisasi Unit Fraseologis Rusia dan Uzbek - Abdukarim S. Musaev (Universitas Muhammadiyah Sidoarjo, 2026)
General Background: In contemporary linguistics, phraseological units are regarded as complex symbolic constructions where lexical meaning, cultural symbolism, and grammatical organization interact within a cognitive-pragmatic framework. Specific Background: Although extensive research has addressed the semantic and conceptual dimensions of phraseology, the grammatical dimension of pragmatic functioning, particularly in comparative perspective, remains underexplored. Knowledge Gap: The role of grammatical categories in activating the pragmatic potential of phraseological units in Russian and Uzbek has not been sufficiently systematized, especially regarding their contribution to illocutionary force, evaluative orientation, and communicative effect. Aims: This study aims to identify and describe grammatical mechanisms of pragmatization in Russian and Uzbek phraseology and to determine their role in shaping communicative meaning. Results: The findings demonstrate that grammatical categories such as person, number, modality, tense, and syntactic configuration operate as regulatory instruments of pragmatic actualization. Grammatical variation modifies illocutionary status, redistributes subject roles, adjusts categoricality, and intensifies evaluative and expressive components without destroying idiomatic identity. Comparative analysis shows that both languages employ similar cognitive-pragmatic mechanisms, despite differences in linguistic realization. Novelty: The study systematizes grammatical pragmatization as a dynamic and regulatory level of phraseological functioning in a cross-linguistic perspective. Implications: The results contribute to cognitive linguistics, comparative phraseology, and pragmatics by clarifying how grammar structures communicative strategies and pragmatic interpretation in discourse. Highlights• Person and number variation restructures discourse roles and communicative perspective.• Modal and syntactic transformation modifies illocutionary status and categoricality.• Cross-linguistic comparison reveals shared cognitive-pragmatic patterns with distinct linguistic realization. KeywordsGrammatical Pragmatization; Phraseological Units; Cognitive Pragmatics; Illocutionary Force; Russian And Uzbek Languages